Faktor - Faktor Pendorong Kemenangan Hassan Rouhani Dalam Pemilu Iran Juni 2013 - Ali Bin Zed (Jurnal Paradigma, 2013)
We can conclude Hassan Rouhani victory in Iran presidential election June 2013 as a victory of the people. Direct impact of iran’s slump in the economic sector due to international sanctions is felt by the people. Hassan rouhani victory is not without reason, there are factors that drive hassan rouhani to win in iran president election June 2013. In this journal the writer will describe the main point of the victory of Hassan Rouhani in Iran president election who held in june 2013.